2018
DOI: 10.1002/jcp.27401
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐382 silencing induces a mitonuclear protein imbalance and activates the mitochondrial unfolded protein response in muscle cells

Abstract: Proper mitochondrial function plays a central role in cellular metabolism. Various diseases as well as aging are associated with diminished mitochondrial function. Previously, we identified 19 miRNAs putatively involved in the regulation of mitochondrial metabolism in skeletal muscle, a highly metabolically active tissue. In the current study, these 19 miRNAs were individually silenced in C2C12 myotubes using antisense oligonucleotides, followed by measurement of the expression of 27 genes known to play a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Other players involved in mitochondrial cross-compartmental signalling could also be promising, although they have not yet been linked to longevity. For instance, silencing the microRNA-382 induced mitonuclear protein imbalance by downregulation of MRPs and this activated UPR mt in muscle cells [98]. More non-coding RNAs are being identified, which also have a modifying role in cross-compartmental proteostasis and could be explored as possible targets to treat age-related diseases [99].…”
Section: Discussionmentioning
confidence: 99%
“…Other players involved in mitochondrial cross-compartmental signalling could also be promising, although they have not yet been linked to longevity. For instance, silencing the microRNA-382 induced mitonuclear protein imbalance by downregulation of MRPs and this activated UPR mt in muscle cells [98]. More non-coding RNAs are being identified, which also have a modifying role in cross-compartmental proteostasis and could be explored as possible targets to treat age-related diseases [99].…”
Section: Discussionmentioning
confidence: 99%
“…Two of these differentially expressed miRNAs (miR-134-5p and miR-382-5p) were previously shown to be associated with mitochondrial function in murine models. 33,34 In a study including the miRNA microarray profiling of renal tissues in diabetic neuropathy mouse model, Qian et al 34 (2018) observed that the up-regulation of miR-134-5p further regulates the mitochondrial apoptosis process by targeting Bcl2 mRNA in podocytes. In addition, silencing of the miR-382 was found to increase the mRNA levels of the genes PPARGC1A (PGC-1a), Sirtuin1 (SIRT1), Mitofusin 1 (MFN1), Mitofusin 2 (MFN2), and optic atrophy 1 (OPA1), and thus regulates mitochondrial biogenesis and dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, silencing of the miR-382 was found to increase the mRNA levels of the genes PPARGC1A (PGC-1a), Sirtuin1 (SIRT1), Mitofusin 1 (MFN1), Mitofusin 2 (MFN2), and optic atrophy 1 (OPA1), and thus regulates mitochondrial biogenesis and dynamics. 33 Although miR-708-5p, miR-497-5p, and miR-199a-5p were shown to be important for the maintenance of skeletal muscle function, 35e37 there are no other studies that describe the relationship between mitochondrial dysfunction and miR-409-3p, miR-497-5p, miR-708-5p, and miR-199a-5p. However, compatible with the current study's findings, three of these differentially expressed miRNAs have been shown to dysregulate in other muscular dystrophies.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional microarray analysis revealed the downregulation of MRPs and respiratory chain proteins in C2C12 myotubes upon silencing of miRNA-382-5p. This effect was accompanied by an imbalance between mitochondrial proteins encoded by nDNA and mtDNA and induction of heat shock protein 60 (HSP60), indicating that UPRmt was activated and that silencing of miR-382-5p resulted in mitonuclear protein imbalance and activated UPRmt in skeletal muscle ( Dahlmans et al, 2019 ). Chloramphenicol and other antibiotics inhibit mitochondrial protein translation, effectively decreasing the synthesis of mitochondrial proteins in INS-1E cells and reducing the expression of mtDNA encoding the COX1 subunit of the respiratory chain, rather than the ATP synthase subunit ATP5PF.…”
Section: Crosstalk Between Mitochondrial and Cytoplasmic Protein Synthesismentioning
confidence: 99%